Characterisation of the chromosome fusions in Oreochromis karongae - Mota-Velasco, Jose C.; Ferreira, Irani Alves [UNESP]; Cioffi, Marcelo B.; Ocalewicz, Konrad; Campos-Ramos, Rafael; Shirak, Andrey; Lee, Bo-Young; Martins, Cesar [UNESP]; Penman, David J. (Springer, 2010)
Oreochromis karongae, one of the "chambo" tilapia species from Lake Malawi, has a karyotype of 2n = 38, making it one of the few species investigated to differ from the typical tilapia karyotype (2n = 44). The O. karongae karyotype consists of one large subtelocentric pair of chromosomes, four medium-sized pairs (three subtelocentric and one submetacentric) and 14 small pairs. The five largest pairs could be distinguished from each other on the basis of size, morphology and a series of fluorescence in situ hybridisation (FISH) probes. The largest pair is easily distinguished on the basis of size and a chromosome 1 (linkage group 3) bacterial artificial chromosome (BAC) FISH probe from Oreochromis niloticus. BAC clones from O. niloticus chromosome 2 (linkage group 7) hybridised to one of the medium-sized subtelocentric chromosome pairs (no. 5) of O. karongae, distinguishing the ancestral medium-sized pair from the three other medium-sized chromosome pairs (nos. 2, 3 and 4) that appear to have resulted from fusions. SATA repetitive DNA hybridised to the centromeres of all 19 chromosome pairs and also revealed the locations of the relic centromeres in the three fused pairs. Telomeric (TTAGGG)(n) repeats were identified in the telomeres of all chromosomes, and an interstitial telomeric site (ITS) was identified in three chromosomal pairs (no. 2, 3 and 4). Additionally, two ITS sites were identified in the largest chromosome pair (pair 1), confirming the origin of this chromosome from three ancestral chromosomes. SATA and ITS sites allowed the orientation of the fusions in pairs 2, 3 and 4, which all appear to have been in different orientations (q-q, p-q and p-p, respectively). One of these fusions (O. karongae chromosome pair no. 2) involves a small chromosome (equivalent to linkage group 1), which in O. niloticus carries the main sex-determining gene. 4',6-Diamidino-2-phenyloindole staining of the synaptonemal complex in male O. karongae revealed the presumptive positions of the kinetochores, which correspond well to the centromeric positions observed in the mitotic karyotype.
Keywords: tilapia; chambo; Malawi; cichlid; FISH; synaptonemal complex; Cyp19b